Leveraging Artificial Intelligence for Competitive Advantage in Indonesian SMEs - Jaya, Aswadi; Cahyono, Dwi; Maria, Lily (Pandawan, 2025)
Artificial Intelligence (AI) has emerged as a transformative force in modern business, offering significant opportunities to enhance operational efficiency, improve customer engagement, and foster innovation. In Indonesia, Small and Medium Enterprises (SMEs) play a crucial role in driving economic growth and employment, yet their adoption of AI technologies remains limited due to resource constraints, lack of expertise, and uncertainty about return on investment. This study aims to investigate how AI adoption can be leveraged to achieve competitive advantage in Indonesian SMEs. Using a mixed-methods approach, data were collected through surveys and in-depth interviews with SME owners across various sectors. The findings indicate that AI applications such as predictive analytics, chatbot-based customer service, and demand forecasting have contributed to increased productivity, cost efficiency, and market competitiveness. The study provides a practical framework for AI implementation tailored to the needs and capacities of Indonesian SMEs, offering insights for business practitioners, policymakers, and researchers seeking to advance digital transformation in the SME sector.